Economic Freedom and Socio-Economic Development in Mexico (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2020)
There is well-founded evidence from various authors, in addition to country comparisons, that economic freedom is essential for the growth and socio-economic development of a nation. Therefore, the main objective of this research is to analyze the socio-economic development of four countries: three that have adopted free market measures and have a capitalist economic system (USA, South Korea), and one with marked state intervention (Argentina), in comparison with Mexico. Through the Economic Freedom Index and its evolution in Mexico, we will analyze whether there has indeed been economic growth as a result. Additionally, a review will be conducted to determine if the current regime (democratic with a presidential government system and a "capitalist" ideology) is efficient for the daily challenges faced, such as high levels of poverty and low educational attainment. Using insights from three economic schools of thought - classical, French, and Austrian - the results indicate that Mexico tends towards greater economic freedom, although it appears biased, as within the parameters (government size, rule of law, regulatory efficiency, and open markets), some results may seem significant (even considered fundamental for economic freedom), but they do not actually affect the final outcome. Thus, it is concluded that despite tending towards greater freedom, economic development is not equitable, as it is largely concentrated for the ruling elite, due to the lack of creation of equal opportunities.